Solve :- 3 / 2 x + 1 = 13

Solve :-

3 / 2 x + 1 = 13

Liked this question? Tell your friends about it

4 Answers

Order by
Oldest to Newest
Newest to Oldest
Votes

Dana answered -1/8, that is the solution to -3/(2x) +1 = 13

My guess is that the problem should be read (-3/2)x +1 = 13 for which the solution is x=-8

It is not entirely clear what is the question.  There are 3 options: 
1.  (-3/2)*X + 1 = 13 
     (-3/2)*X = 12 
      -3X = 24
       X = -8
2.  -3/(2X) + 1 = 13
     -3/(2X) = 12
      -3 = 24X
       X = -1/8
3.  -3/(2X+1) = 13
     -3 = 26X +13
      -16 = 26X
      X = -8/13
       

Love is the battery of life....

3 / 2 x + 1 = 13

3 / 2 x=12

x=12*2/3=8

Related Questions

Other people asked questions on similar topics, check out the answers they received:

Asked: What will be the development trend of mining ...

Withthe rapid development of science and technology, we have entered the digital information age.This is known to all that informatization has four characteristics , namely intelligent , electronic ...

Asked: How do I solve this simultaneous equation. Been a ...

-462=x-y x=-2y The question is with regards to a three bar model and the residual stress in welds. The answer is: x=-154 MPa and y is +308 MPa x is actually stress2 and y is stress1 I'm so ...

Asked: What is the mathematical term for 9 squared ...

what is the mathematical term for 9 squared multiplied by b squared equals c squared?

More Questions

Brickmold 2-1/4"

We've run into this same challenge on a couple projects. Older brickmold was milled with a 2 1/4" wide face and all the new "off the shelf" brickmold is 2". We found original brickmold both times at a salvage yard here in Oregon. Do you have building material salvage yards in your locale? I've ...

1:3 questions, and 1:2 answers....... Come from ...

As predicted, the neurotic has posted 7:1 but has proved nothing, other than the fear and hatred of neurotic leftists. It is most reassuring to see that I am still quite sensible and compassionate despite the rash and bitter abuses of paranoid leftists. That really does make me the better man for ...

Solve f(x)= 2(1/2)-6

f(x) = 2*(1/2) - 6 f(x) = 1 -6 f(x) = -5 But there is a "problem". f(x) is an expression that is a function of X..... that means that the value of that function ( = f[x]) will get different values for different X's. Here f(x) has a constant value ( = 5) and is not a function of X..... so ...

How do you solve 3/4(x+8)=1/2x+3.5

I hope that you mean: (3/4)*(X+8) = (1/2)*X + 3.5 If that is what you mean than: Multiply both sides by 4 to get (the puppose is to get rid of the fractions..... make life easier): 3*(X+8) = 2*X + 14 3X + 24 = 2X + 14 3X - 2X = 14 -24 X = -10